Heritabilities and correlations of deformities and growth‐related traits in the European sea bass (Dicentrarchus labrax, L) in four different sites. Issue 2 (30th January 2012) - Karahan, Bilge; Chatain, Béatrice; Chavanne, Hervé; Vergnet, Alain; Bardon, Agnès; Haffray, Pierrick; Dupont‐Nivet, Mathilde; Vandeputte, Marc
Abstract Skeletal deformities are important traits for aquaculture as they induce slow growing and low market value. We studied their genetic determinism and their interactions with the environment at the ongrowing stage in 5839 European sea bass from a partial factorial mating of 33 sires and 23 dams, reared in four sites. All families were mixed, and fish were first reared in one site (site B) until 35 g mean weight, then distributed to the four sites. A posteriori reconstruction of pedigree with microsatellites was used. Deformities were scored internally at slaughtering, and externally from photographs. Site B, where all fish were initially stocked until 35 g and exposed to forced swimming because of fast water current showed the highest rate of deformities with 83% and 65% from internal and external scoring respectively. Heritability on the underlying scale was h2 = 0.25 ± 0.03 across all sites, and varied little between sites, while genetic correlations of deformities between sites were always high (>0.85). Genetic correlations between deformities and daily growth coefficient were variable between sites(rA = 0.50 ± 0.09, 0.43 ± 0.10, 0.32 ± 0.10, 0.18 ± 0.10 for sites A, B, C, D respectively) and were positively linked with the average growth rate in each site. These results pointed out that there could be a relation between growth rate and the evolution of deformities at the grow‐out stage.